Synthesis, Biological Evaluation and Molecular Modeling Studies of New 2, 3‐Diheteroaryl Thiazolidin‐4‐Ones as NNRTIs. (22nd July 2015) - Debnath, Utsab; Verma, Saroj; Singh, Pankaj; Rawat, Kavita; Gupta, Satish K.; Tripathi, Raj K.; Siddiqui, Hefazat H.; Katti, Seturam B.; Prabhakar, Yenamandra S.
Abstract : In a focused exploration, thiazolidin‐4‐ones with different C‐2 and N‐3 substituent groups were synthesized and evaluated as non‐nucleoside reverse transcriptase inhibitors against HIV‐1. This has led to new active compounds sporting heteroaryls at both C‐2 and N‐3 positions prompting to view them in the backdrop of nevirapine. To assign the molecular attributes for the activity, the compounds are investigated by docking them into non‐nucleoside inhibitor‐binding pocket of HIV‐1 reverse transcriptase (RT). The most active compounds of this series (7d and7f ) shared spatial features with nevirapine with added molecular flexibility. Furthermore, in molecular dynamics simulations carried out for up to 10 ns, the compounds7d and7f showed consistency in their interactions with non‐nucleoside inhibitor‐binding pocket of HIV‐1 RT and suggested Tyr319 and Val106 as potential residues for H‐bond interaction with these molecules. These results open new avenues for the exploration of 2, 3‐diheteroaryl thiazolidin‐4‐ones for prevention of HIV‐1. Abstract : Thiazolidin‐4‐ones with different C‐2 and N‐3 substituent groups were synthesized and evaluated as non‐nucleoside reverse transcriptase inhibitors of HIV‐1. This has led to new active compounds sporting heteroaryls at both C‐2 and N‐3 positions prompting to view them in the backdrop of nevirapine. The most active compounds (7d and7f ) shared spatial features with nevirapine. Molecular dynamics simulations carried out on HIV‐1 reverse transcriptase – compound (7d and7f ) complex identified avenues to design new 2, 3‐diheteroaryl thiazolidinon‐4‐one against HIV‐1.